Reporting Sexual Assault: Can Knowledge of How to Protect Forensic Evidence Influence Intentions to Report? - McQueen, Emma J. (Journal of interpersonal violence, 2021)
Responding to the high prevalence, low reporting, and poor conviction rates of adult sexual assault, Australian criminal jurisdictions have introduced protocols that allowed collection of medical forensic evidence from victims without police notification, since 1999. To assess the influence of reforms on potential victim behavior, this study measured lay knowledge of measures to protect forensic evidence of sexual assault, and predictors of intention to report adult sexual assault through the lens of the theory of planned behavior (TPB). An online survey was conducted with a sample of University of Canberra students and community members (N = 204). Results indicated moderate lay knowledge of how to protect evidence of sexual assault; however, only 46.1% of the sample were aware that evidence could be collected without police notification. The TPB successfully explained 55.6% of variance in intention to report future sexual assault. Participants who had experienced previous adult sexual assault victimization were significantly less likely to intend to report future sexual assault than those who had not. Knowledge of forensic evidence of sexual assault was not related to intention to report by self-efficacy as predicted; instead, it was mediated via subjective norms. Results indicated the potential value education to improve lay awareness of how to protect and report medical forensic evidence and to foster social norms that value reporting, particularly among school and university students.